Cost-Effectiveness Analysis of Simvastatin and Atorvastatin in Hypertensive patients with type 2 Diabetes Mellitus Comorbidities at KHZ Musthafa Regional Hospital: from the provider’s perspective - Dheana Ratu Hazlisa; Nur Rahayuningsih; Citra Dewi Salasanti (Jurnal Ilmiah Farmako Bahari, 2026)
Hypertension with comorbid type 2 diabetes mellitus is a chronic condition strongly associated with an increased risk of cardiovascular complications, such as coronary heart disease, stroke, and vascular damage. This condition requires pharmacological therapy that is not only clinically effective but also cost-effective in terms of healthcare services. In clinical practice, statins such as simvastatin and atorvastatin are frequently used as lipid-lowering therapy to help reduce the risk of cardiovascular complications in patients with metabolic diseases. However, differences in treatment costs and clinical outcomes between these two medications make pharmacoeconomic evaluation crucial in determining the most cost-effective therapeutic option. This study aims to analyze the cost-effectiveness of simvastatin and atorvastatin use in hypertensive patients with type 2 diabetes mellitus comorbidity from the perspective of healthcare providers at KHZ Musthafa Regional General Hospital, Tasikmalaya. This study employed a retrospective cross-sectional design based on medical records and patient billing data from January 2024 to December 2025. Using purposive sampling, 57 patients who met the inclusion criteria were included in the study. Cost-effectiveness analysis was performed by calculating direct medical costs, therapeutic effectiveness based on the average length of hospital stay (LOS), the Average Cost-Effectiveness Ratio (ACER), and the Incremental Cost-Effectiveness Ratio (ICER). The results showed that the group of patients receiving simvastatin had lower direct medical costs, namely Rp4,269,569, compared to the atorvastatin group at Rp5,902,031. In addition, the simvastatin group also showed a shorter average length of stay, namely 3.8 days, while the atorvastatin group reached 4.7 days. The ICER for simvastatin was recorded at Rp1,123,570 per day, which is lower than that of atorvastatin at Rp1,255,751 per day. Based on these results, simvastatin is considered more cost-effective than atorvastatin in hypertensive patients with type 2 diabetes mellitus, making it a potentially more efficient therapeutic option for hospitals.